The impact of Canva-assisted project-based learning on IPAS learning results - Farah Amelia; Desak Made Darmawati (Curricula: Journal of Curriculum Development, 2025)
The Canva-assisted project-based learning model is an innovation for teachers to make learning interactive with the help of technology in the digital era of education. This model integrates Canva as a project of the learning process. This research was conducted because of the low learning outcomes of Natural and Social Sciences (IPAS) grade 5 SDN Jatibening 4 Bekasi on the material of the parts of the eye. This research was conducted through a quantitative experimental method with a quasi-experimental design involving an experimental class and a control class, both of which were given a pretest and a post-test. The findings of this study indicate that the project-based learning model assisted by Canva has a significant effect on the achievement of IPAS learning outcomes in grade 5 SDN Jatibening 4 Bekasi. The conclusion obtained is that the experimental class and control class have different average learning outcomes. The average value of the experimental class exceeds the average value of the control class, so it can be said that the Canva-assisted project-based learning Model is proven effective in the learning process in the classroom.   Abstrak Model project based learning berbantuan Canva ialah sebuah inovasi bagi guru untuk membuat pembelajaran menjadi interaktif dengan bantuan teknologi di pendidikan era digital. Model ini mengintegrasikan Canva sebagai proyek dari proses pembelajaran. Penelitian ini dilakukan karena rendahnya hasil belajar Ilmu Pengetahuan Alam dan Sosial (IPAS) kelas 5 SDN Jatibening 4 Bekasi pada materi bagian-bagian mata. Penelitian ini dilaksanakan melalui metode kuantitatif eksperimen dengan desain Quasi Experimental Design yang melibatkan kelas eksperimen dan kelas kontrol yang keduanya akan diberikan pretest dan post-test. Temuan dari penelitian ini mengindikasikan model project based learning berbantuan Canva memberikan pengaruh secara signifikan terhadap pencapaian hasil belajar IPAS kelas 5 SDN Jatibening 4 Bekasi. Kesimpulan yang didapatkan yaitu kelas eksperimen dan kelas kontrol mempunyai rata-rata hasil belajar yang berbeda. Nilai rata-rata kelas eksperimen melebihi nilai rata-rata kelas kontrol sehingga dapat dikatakan model project based learning berbantuan Canva terbukti efektif untuk diterapkan dalam proses pembelajaran di dalam kelas. Kata Kunci: Canva; hasil belajar; IPAS; project-based learning